Synthesis of Hydroxyapatite from Green Mussel Shells Using Micro-wave Method Through Ultrasonic Mixing Process and Magnetic Stirrer Stirring - Risky Ismail; A. P. Bayuseno; Samsudin Anis; Deni Fajar Fitriyana; Muhammad Afrizal; Januar Parlaungan Siregar; Agus Prasetyo (Universitas Negeri Semarang, 2025)
Hydroxyapatite (HAp) is a biomaterial containing calcium phosphate with the chemical formula which is similar to the structure of human bone, so it is good for the purpose of healing human bones and teeth. HAp synthesis has several methods that can affect the results of HAp synthesis, such as the method of mixing CaO with phosphate, namely mixing with ultrasonic machines and magnetic stirrers. However, the discussion about the difference of HAp results with the mixing method of ultrasonic machine and magnetic stirrer is still rarely done. Therefore, it is important to examine and compare the characteristics of HAp synthesized by ultrasonic and magnetic stirrer mixing. The result of XRD test shows that HA1 has a purity of weight percentage (wt.%) of HAp crystal of 99.8%, while HA2 has a weight percentage (wt.%) of HAp crystal of 97.7%. For the FTIR test results of both specimens detected the presence of phosphate groups, and hydoxide, where both are the basic form of hydroxyapatite. Carbonate groups were also detected in the test, but it cannot be said to be bad because carbonate is a natural substitute for phosphate.